Do ser ao fazer: infância e família sob a perspectiva da socialização da linguagem - Schnack, Cristiane Maria (Universidade do Vale do Rio do Sinos, 2006)
Some studies concerning language acquisition have shown that adult-child and adult-adult interactions are distinctly constituted so as to provide children a facilitated access to the complex linguistic structure (e.g. SNOW e FERGUSON, 1977; FERGUSON, 1996). Others have tried to understand children's pragmatic development of language throughout their first years of life (e.g. ERVIN-TRIPP, 1979; CORSARO, 1979), revealing the (evolving) competence of these children in realizing certain speech acts (AUSTIN, 1999). This research departs from those studies and broadens the research perspectives by considering that learning a language is constitutive of the process of becoming a member of a group (OCHS, 2002). The (linguistic-pragmatic) development process of a child is thus linked to the (interactional) practices in which the child is engaged, as are the other members of the group. From a micro-ethnographic perspective, rooted in theoretical and analytical presuppositions implied in the analysis of face-to-face int
Keywords: aprendizagem; criança; desenvolvimento; ensino; família; interação; interação adulto; linguagem falada; socialização; linguagem; child development; childhood; family; talk-in-interaction; language socialization; Letras e Artes; Lingüística